2003
DOI: 10.1016/s1475-4916(03)00007-9
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic aggravations: a systematic review of randomised, placebo-controlled clinical trials

Abstract: Homeopathic aggravations have often been described anecdotally. However, few attempts have been made to scientifically verify their existence. This systematic review aimed at comparing the frequency of homeopathic aggravations in the placebo and verum groups of double-blind, randomised clinical trials. Eight independent literature searches were carried out to identify all such trials mentioning either adverse effects or aggravations. All studies thus found were validated and data were extracted by both authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 23 publications
0
36
1
1
Order By: Relevance
“…Grabia and Ernst (24) found in a systematic review of homeopathic aggravations in 25 placebo-controlled RCTs, 33 adverse effects in the placebo groups and 97 in the homeopathy groups. No grading of the adverse effects was given in the article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grabia and Ernst (24) found in a systematic review of homeopathic aggravations in 25 placebo-controlled RCTs, 33 adverse effects in the placebo groups and 97 in the homeopathy groups. No grading of the adverse effects was given in the article.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is seen as a favourable response to the treatment and is expected to be followed by an improvement (2,(21)(22)(23). In 2003, Grabia and Ernst (24) published a systematic review to investigate how homeopathic aggravations was reported in RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Naturopathy is guided by an interesting arrangement of the rule that perceives the body's inborn healing capacity, emphasizes disease prevention, and urges singular responsibility to get ideal wellbeing. Naturopathic hypothesis, the disease is seen as a procedure of disturbance to well-being and consequent recovery with regard to natural healing systems [40].…”
Section: Yoga and Naturopathymentioning
confidence: 99%
“…Many good quality studies of the last 12 years have yielded negative results, for instance, concerning systematic reviews and meta-analyses 32,33 ; bruising 34,35 ; anxiety 36 ; "provings" (see below) with belladonna, arnica, Pulsatilla and mercury 37-41 and "aggravations" ("good" worsening of symptoms, said by homeopaths to precede patient recovery) 42 . Detailed comments on many of these studies are published 2,5,43 .…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Many good quality studies of the last 12 years have yielded negative results, for instance, concerning systematic reviews and meta-analyses [3][4][5][6][7][8][9][10][11] ; infections of the upper respiratory tract and allergic rhinitis 12,13 ; post-operative ileus 14 ; asthma 15 ; warts [16][17][18] ; pain relief and muscle soreness [19][20][21][22][23] ; treatment of adenoid vegetation 24 ; chronic headache [25][26][27][28] ; ear inflammation 29,30 ; eczema 31 ; arthritis 32,33 ; bruising 34,35 ; anxiety 36 ; "provings" (see below) with belladonna, arnica, Pulsatilla and mercury [37][38][39][40][41] and "aggravations" ("good" worsening of symptoms, said by homeopaths to precede patient recovery) 42 . Detailed comments on many of these studies are published 2,5,43 .…”
Section: Clinical Trialsmentioning
confidence: 99%